Reactive Oxygen Species (ROS)-Responsive Biomaterials for the Treatment of Bone-Related Diseases - Ren, Xiaoxiang; Liu, Han; Wu, Xianmin; Weng, Weizong; Wang, Xiuhui; Su, Jiacan (Frontiers in Bioengineering and Biotechnology, 2022)
Reactive oxygen species (ROS) are the key signaling molecules in many physiological signs of progress and are associated with nearly all diseases, such as atherosclerosis, aging, and cancer. Bone is a specific connective tissue consisting of cells, fibers, and mineralized extracellular components, which quality changes with aging and disease. Growing evidence indicated that overproduced ROS accumulation may disrupt cellular homeostasis in the progress of bone modeling and remodeling, leading to bone metabolic disease. Thus, ROS-responsive biomaterials have attracted great interest from many researchers as promising strategies to realize drug release or targeted therapy for bone-related diseases. Herein, we endeavor to introduce the role of ROS in the bone microenvironment, summarize the mechanism and development of ROS responsive biomaterials, as well as their completion and potential for future therapy of bone-related diseases.